Pilot study evaluating lipoma reduction with injected physiologic ice slurry - Arango, Kristen K.; London, Cheryl A.; Karlin, William M.; Hicks, Jacqueline Milton (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to assess the adverse event profile following injection of canine lipomas with BXT-786 coolant, and to assess its impact on lipoma size.MethodsTen healthy adult client-owned animals, each with two similarly sized, cytologically confirmed lipomas were enrolled. Lipomas were injected with either BXT-786 coolant or control room temperature 0.9% saline solution. Two blinded, independent observers measured lipomas with a caliper and ultrasound. Dogs were reevaluated at 2, 4, 8, and 12-weeks post-injections to assess for adverse events and repeat measurements. Lipomas were surgically removed at 12 weeks post injection and submitted for histopathologic analysis. Health related quality of life was assessed using an owner completed questionnaire. Response to treatment was determined and adverse events were reported and graded.ResultsBased on caliper assessment, majority of the lipomas were determined to be stable in size prior to surgical excision after BXT-786 or saline injection. Greater variability in response assessment was observed when using ultrasound. No statistically significant change was found in patient quality of life over an 8-week period. Adverse events were typically unrelated to BXT-786 injection, although one dog did develop cellulitis and mild necrosis in the lipoma.ConclusionInjection of BXT-786 coolant into lipomas was feasible and did induce some histopathologic changes consistent with effects on tumor cells, but it did not result in tumor shrinkage. Future studies could explore using coolants with more sustained coolant function and multiple injections to promote more efficient tumor reduction.